Al 6063 hybrid metal matrix reinforced composites with TiC nanoparticles and NEEM leaf ash using stir casting method for bicycle frame - Vates, Umesh Kumar; Khattar, Nirav; Kumar, Rohit; Bhardwaj, Ansh; Sharma, Bhupendra Prakash; Kanu, Nand Jee; Gupta, Eva; Singh, Gyanendra Kumar; Subramaniam, Sivaraos (2002)
Aluminium metal matrix composites (AMMCs) are the trustful materials for marine, aerospace, defence, advanced structural, aviation applications and also in automobile vehicles due to its favourable properties. The hybrid metal matrix composites are manufactured using stir casting process, which is the simplest and most convenient form of manufacturing a material. In this present research work, aluminium alloy 6063 has been bolstered with TiC and neem leaf ash. Seven samples have been fabricated sample 1 (Al 6063 hundred%), sample 2 (Al 6063 ninety-five% + TiC 4% + neem ash 1%), sample 3 (Al 6063 ninety-six and half % + TiC 2% + neem leaf ash 1.5%), sample 4 (Al 6063 ninety-three and half % + TiC 6% + neem leaf ash half%), sample 5 (Al 6063 ninety-seven and half % + TiC 2% + neem leaf ash half %), sample 6 (Al 6063 ninety-five and half % + TiC 4% + neem leaf ash half %) and sample 7 (Al 6063 ninety-three% + TiC 6% + neem leaf ash 1%). After manufacturing these samples, the hardness test, strength and fatigue test have been conducted. Optimal combination of TiC and neem leaf ash particles in the Al matrix is improving mechanical properties as per the desire for bicycle frame.